globos sonda. - Zaya, Octavio; Pérez Rubio, Agustín; Gerveno, Marta (León : MUSAC. Museo de Arte Contemporáneo de Castilla y León, 2006)
Alves, Dino ; AMID* architecture (cero9) ; Aranda, Julieta ; AVAF - assume vivid astro focus ; AVPD ; Brand, Eelco ; Buche, Tobias ; Double standards / Rehberger, Chris ; Dr. Hofmann ; Dreyfus, Smadar ; Emmerich, Hadassah ; Escudero, Inazio ; Farid, Heba ; Favaretto, Lara ; Förster, Gunda ; Funky projects ; Gander, Ryan ; Göngrich, Erik ; Just, Jesper ; King / de León, Diaz ; Kooi, Ellen ; Kyupi Kyupi ; Lang / Baunmann ; Lemos Auad, Tonico ; de la Barra, Pablo León ; Lin, Shu-min ; Liu, Jen ; Löfström, Katarina ; López, Juan ; Marzouk, Mona ; Masakatsu, Takagi ; Masip, Ángel ; Meckseper, Josephine ; Nashat, Shahryar ; Navratil, Alexandra ; Oligatega Numeric ; Núñez Pombo, Ángel ; PSJM ; Renes, Fernando ; Ruiz, Francesc ; Schinwald, Markus ; Shearer, Steven ; Superm (Mogutin, Slava & Kenny, Brian) ; Tabata, Kouichi ; Fresh, Topacio ; Violette, Banks ; Weissman, Nadav ; Wulia, Tintin
globos sonda - trial balloons, MUSAC, Museo de Arte Contemporáneo de Castilla y León, Léon, May 6th - September 10th, 2006
boek